BAHAN PANGAN UNTUK PEMBELAJARAN BAGI SISWA IPA DI SMP DAN SMA DI KABUPATEN KEEROM, PAPUA - Purnamasari, Vita; Sujarta, Puguh; Farmawaty, Farmawaty; Rahayu, Irma; Mantek, Mesak; Daryati, Siti (JURNAL PENGABDIAN PAPUA, 2024)
Teachers as the driving force in implementing the curriculum are expected to be creative, innovative, and skilled in learning and able to use technology to support continuous improvement of quality and improvement of learning practices. The chemical properties of compounds in food ingredients are known to be able to be used as tools or samples in the implementation of science (science) practicums. Introduction to natural resources, including food ingredients, which are in the school environment or students' homes as part of the learning experience from the environment and as objects in learning projects for teachers is considered important to do. The purpose of this activity is to provide teachers with an introduction and experience about the use of food ingredients in science learning, especially in biology and chemistry (science) studies. Teachers are the first party to benefit from this activity. Furthermore, together with teachers as facilitators, students, in the form of learning projects, can learn through their direct experiences using materials around them. The implementation of community service is carried out using two methods, namely the socialization method and the training method. Socialization is carried out to introduce the characteristics of food ingredients, namely butterfly pea flowers, red spinach, bread yeast, pineapple and coconut milk. The training is intended to provide direct experience to teachers so that they can be implemented in science learning in their respective schools. Keywords: pembelajaran IPA; bahan pangan; Kabupaten Keerom